CONDENSED TANNINS EXTRACTED OF EUCALYPTS BARK WASTE - Santiago, Sabrina Barros; Gonçalves, Fabricio Gomes; Paes, Juarez Benigno; Lelis, Roberto Carlos Costa; Vidaurre, Graziela Baptista; Arantes, Marina Donária Chaves (Floresta, 2018)
This work aimed evaluate the quality and quantity tannins contained from the eucalypts bark waste. The tannins were extracted with water and aqueous solutions under different concentrations (0, 4, 6, 8 and 10%) of sodium sulfate and sodium carbonate. The influence of the different concentrations of chemical compounds (Na2SO4 and Na2CO3), on yield and extract characteristics, namely: total solids content, tannins yield, non-tannins yield, pH, polyphenols yield by Stiasny reaction and reactive polyphenols contents by ultraviolet method. The results obtained showed that the sodium carbonate solution (8%) provided higher tannins extraction and sodium sulfate solution (4%) the lower amounts. The influence of 8% sodium carbonate on the eucalypts bark characteristics in extraction provided highest Stiasny number and tannins content, in addition, were achieved high extraction yield, indicating the importance of use this concentration of salt in the extraction process. While for sodium sulfate the highest gravimetric yield in tannins was 4%. The eucalypt bark may be used in tannins extraction for being available and allowing a good yield in tannin.